Pacemaker‐mediated arrhythmias - Alasti, Mohammad (J Arrhythm, 2018)
Pacemakers can be directly involved in initiating or sustaining different forms of arrhythmia. These can cause symptoms such as dyspnea, palpitations, and decompensated heart failure. Early detection of these arrhythmias and optimal pacemaker programming is pivotal. The aim of this review article is to summarize the different types of pacemaker‐mediated arrhythmias, their predisposing factors, and mechanisms of prevention or termination.